2019
DOI: 10.3389/fpls.2019.00581
|View full text |Cite
|
Sign up to set email alerts
|

Phytolith-Occluded Carbon Storages in Forest Litter Layers in Southern China: Implications for Evaluation of Long-Term Forest Carbon Budget

Abstract: Phytolith-occluded carbon (PhytOC) can be preserved in soils or sediments for thousands of years and might be a promising potential mechanism for long-term terrestrial carbon (C) sequestration. As the principal pathway for the return of organic matters to soils, the forest litter layers make a considerable contribution to terrestrial C sequestration. Although previous studies have estimated the phytolith production fluxes in the above-ground vegetations of various terrestrial ecosystems, the storages of phytol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…A recent study (Chen et al., 2018) reports that the belowground biomass in a bamboo forest accounts for 39.41% of the total plant biomass. Another recent study (Zhang et al., 2019) shows that the litter layer in bamboo forest plays an important role as PhytOC storage. In native steppes, plant aboveground biomass turns to litter in current year, while the belowground biomass is huge and accumulated over multiple years (Chai et al., 2014; Dai et al., 2012; Hou et al., 2014).…”
Section: Discussionmentioning
confidence: 96%
“…A recent study (Chen et al., 2018) reports that the belowground biomass in a bamboo forest accounts for 39.41% of the total plant biomass. Another recent study (Zhang et al., 2019) shows that the litter layer in bamboo forest plays an important role as PhytOC storage. In native steppes, plant aboveground biomass turns to litter in current year, while the belowground biomass is huge and accumulated over multiple years (Chai et al., 2014; Dai et al., 2012; Hou et al., 2014).…”
Section: Discussionmentioning
confidence: 96%
“…All of this causes the SOC content of forest to be higher than that of shrublands and grasslands. Moreover, due to the higher coverage of herbaceous vegetation and abundant species density (Table 1), more surface litter increases the sources of organic carbon (Zhang et al., 2019), making the SOC content of desert grassland vegetation higher than that of both HR and CK vegetation. Meanwhile, the SOC content of the four vegetation types was not only due to organic carbon inputs, but was also affected by enzyme activities and soil physical–chemical characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few decades, extensive efforts at restoring the environment have improved the fragile natural ecosystems on the Loess Plateau (Intergovernmental Panel on Climate Change, 2014). Vegetation restoration not only benefits for water preservation and reduction of soil erosion (Ran et al, 2013), but significantly improves the properties and quality of soil (Zhang et al, 2019). Studies have shown that returning farmland to forests not only improves the SOC reserves and quality, but also improves the conversion trend of soil SOC-related fractions (Deng et al, 2019;Liu et al, 2014;Xun et al, 2010).…”
mentioning
confidence: 99%
“…It may be that a modified form of Equation 1 could be used in these circumstances to determine the overall PhytOC percentage. Very recently, Zhang et al (2019) showed the importance of bamboo litter layers in carbon sequestration, and demonstrated the considerable potential that exists to increase carbon sequestration in the future. But what types of phytoliths might we expect to dominate the litter layers?…”
Section: A Hypothesismentioning
confidence: 99%